Resonance Frequency Analysis of a Mini Tesla Coil (15V–24V) as a High-Voltage Transmitter Prototype - Raihan Fiqri Rhenaputra; Ajie Alvido Akraam; Safira Kania Saraswati (Indonesian Journal of Electrical Engineering and Electronics, 2026)
This study aims to analyze the resonance frequency of the Tesla Coil module based on experiments and theoretical calculations, and provide recommendations for improving the resonance design. The theoretical resonance frequency is calculated at 130.1 kHz, while experimental measurements show a deviation of 5–10%, caused by component tolerance, passive losses, and parasitic effects. Power transfer efficiency increases with input voltage, reaching 82% at 24 V. Analysis using a Quality Factor (Q) of 21.6 and a primary-secondary inductance ratio of 13.6:1 shows good resonance performance but can still be improved. Recommendations for improvement include selecting components with lower tolerances, adjusting capacitance and inductance values, and optimizing PCB design to reduce parasitic effects. The results of this study are expected to be a reference in the development of more efficient and accurate Tesla Coil modules.